A rare presentation of escitalopram overdose-induced bradycardia and arrhythmia in a patient with severe depression - Anand Bhogaraju; Yasaswi Kadaru; Tabitha Jezreel (Telangana Journal of Psychiatry, 2025)
Escitalopram is the most commonly used selective serotonin reuptake inhibitor. Escitalopram toxicity leads to serotonin syndrome, seizures, and cardiac side effects which include QTc prolongation, arrhythmias, and bradycardia. We report the case of a 21-year-old female diagnosed with severe depression, hospitalized for 1 week, after ingesting 10 tablets of 10 mg escitalopram (100 mg). Her electrocardiogram findings on the day of admission initially showed bradycardia with no arrhythmia. After a few hours, the patient developed an arrhythmia, bordering on bradyarrhythmia, possibly ongoing to bradyarrhythmia. The patient was kept under observation and routine laboratory tests including serum electrolytes were normal. This finding disappeared within a few days of stopping escitalopram.